A stellar configuration in Gonyleptidae: Nyctaster, a new genus of Neopachylinae from the Brazilian Atlantic rainforest (Arachnida: Opiliones) - Carvalho, Rafael N.; Kury, Adriano B. (Zootaxa, 2025)
We describe Nyctaster gen. nov., a new genus of Gonyleptidae (Neopachylinae) from southern Brazil, comprising two new species: Nyctaster lanceatus sp. nov. from São Paulo state, and Nyctaster sidereus sp. nov. (type species) from Paraná state. The genus is diagnosed by a unique combination of morphological characters, including a gamma-pyriform dorsal scutum, the presence of a secondary basal branch on the prodorsal apophysis of coxa IV, and male genitalia with spines on the central portion of the stylus. To assess the systematic position of the genus, we conducted a cladistic analysis, with a final character matrix comprising 42 taxa, 104 characters, 3693 scorings, 38 missing data points, and 637 non-applicable entries. Analyses under equal and implied weights (k = 1–20) consistently recovered Nyctaster gen. nov. as monophyletic, sister to Senu Carvalho & Kury, and nested within Neopachylinae. Although morphologically close to Senu, Nyctaster gen. nov. is distinguishable by characters such as a single pair of paramedian tubercles on scutal area I and a paramedian pair of elevated sub-conical blunt apophyses on scutal area III. Distribution data suggests allopatry between the species of Nyctaster, though future collections may improve this pattern. N. lanceatus sp. nov. is known only from the male holotype, while N. sidereus sp. nov. is described on multiple specimens collected in both well-preserved and degraded forest remnants. The results support the inclusion of Nyctaster gen. nov. in Neopachylinae and contribute to a refined understanding of internal relationships within the DRMN clade.